2008
DOI: 10.1080/10715760802571988
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids modulates oxidative damage and mitochondrial dysfunction in diabetic rat brain

Abstract: Diabetes exacerbates neuronal injury induced by hyperglycemia mediated oxidative damage and mitochondrial dysfunction. The aim of the present study is to investigate the effects of curcuminoids, polyphenols of Curcuma longa (L.) on oxidative stress and mitochondrial impairment in the brain of streptozotocin (STZ)-induced diabetic rats. A marked increase in lipid peroxidation and nitrite levels with simultaneous decrease in endogenous antioxidant marker enzymes was observed in the diabetic rat brain, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 41 publications
1
15
0
3
Order By: Relevance
“…It has been shown that curcumin exerts a protective effect in several models of oxidant damage [14][15][16] including isoproterenol-induced cardiac injury [17] and I/R injury in rabbits [40]. Our data are consistent with these previous findings pointing to the attenuation of oxidant stress, which is a key finding in the protective effect of curcumin.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…It has been shown that curcumin exerts a protective effect in several models of oxidant damage [14][15][16] including isoproterenol-induced cardiac injury [17] and I/R injury in rabbits [40]. Our data are consistent with these previous findings pointing to the attenuation of oxidant stress, which is a key finding in the protective effect of curcumin.…”
Section: Discussionsupporting
confidence: 95%
“…Phase II enzymes including glutathione peroxidase, glutathione reductase (GR), glutathione S-transferase (GST), c-glutamate cysteine ligase, and NADPH quinone oxidoreductase 1 protect cells from stress by diminishing oxidant stress or detoxifying carcinogens [11], and curcumin has shown to increase the expression of these enzymes by inducing nuclear translocation of the transcription factor Nrf2 (NF-E2-related factor-2) [12,13]. Several studies have shown that curcumin is able to ameliorate mitochondria-induced ROS production and lipid peroxidation in different models of oxidant damage [14][15][16], including that occurring in cardiac tissue [17,18]. In this respect, several reports have shown that mitochondria are both targets and sources of myocardial damage during ischemia and reperfusion [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Curcuminoids exhibit a protective effect by accelerating anti-oxidant defence mechanisms and attenuating mitochondrial dysfunction in the brain of diabetic rats (Rastogi et al 2008). According to Meghana et al (2007) and Kanitkar et al (2009), curcumin protects pancreatic islets cells against streptozotocininduced death and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…425and complex I and IV activities(Rastogi et al, 2008). Similarly, curcumin administration (15 and 426 30mg/kg body weight/day for 6 weeks) improved oxidative defence, activities of respiratory 427 complexes I, II and III as well as cognitive tasks in a D-galactose induced mouse model of has been reported to have positive effects on mitochondrial function in 434 various animal studies (see above).…”
mentioning
confidence: 94%